The influence of marketing technology on the organisational design of marketing functions in South African banks - Chabalala, Tlangelani (University of the Witwatersrand, Johannesburg, 2022)
The increasing use of marketing technologies in understanding customers and interacting with customers or potential customers has significantly benefitted organisations. These types of technology disruptions are forcing marketing functions to change how they operate. Organisations are faced with the challenges of integrating these technologies into marketing functions and ensuring that they are effectively used. This qualitative study was aimed at understanding the influence of marketing technologies on the design of marketing functions of banking organisations within South Africa. Highlight the challenges and benefits of marketing technologies and suggest recommendations for the effective use of marketing technologies. The study reviewed literature related to understanding the integration of IT into Marketing, new-age technologies and their impact on marketing, and the shift in marketing functions. The study collected data by interviewing 10 senior marketing professionals working within the banking sector. The findings of the study indicate that marketing technologies have introduced new skills and roles within marketing functions. Requiring marketers to upskill themselves in areas such as data analysis and tech-savvy. Marketing technologies had led to a change in marketing function structures and play an important role as input to how marketing functions are designed in banking organisations
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, University of the Witwatersrand, 2022
Keywords: Martech; Marketing Technology; Marketing capabilities; Digital Marketing; IT in Marketing; SDG-8: Decent work and economic growth